Mad at Microsoft. (Economist, 1992)
This article reports that Microsoft Corp., the computer software industry's biggest firm, has outraged competitors by allegedly hiding sets of instructions in its popular Microsoft Windows operating-system software. A book published a few months ago called "Undocumented Windows" claims that Microsoft's own spreadsheets, and other applications, take advantage of features of Windows which are not reported in the documentation. Windows does no actual work itself. It is a program which makes other programs easier to understand and use. Windows in turn is based on Microsoft's MS-DOS operating system.